Reinfection with SARS‐CoV‐2 in solid‐organ transplant recipients: Incidence density and convalescent immunity prior to reinfection. Issue 3 (6th April 2022) - Morris, Stephen; Anjan, Shweta; Pallikkuth, Suresh; Frattaroli, Paola; Courel, Steve; Fernandez, Anmary; Natori, Akina; Abbo, Lilian; Pahwa, Savita; Guerra, Giselle; Natori, Yoichiro
Abstract: Background: Long‐term protective immunity to severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) remains poorly characterized, particularly in solid organ transplant (SOT) patients. Method: We determined the incidence density of SARS‐CoV‐2 reinfection in a cohort of adult SOT recipients initially infected between March 1st, 2020 and March 30th, 2021 and included those with initial infection before or after transplantation. Incidence density was the total cases divided by total days after initial diagnosis with active graft. Results: Of 210 infected recipients, five (2.4%) developed reinfection, including two who had received full mRNA vaccination, but none developed hypoxia. The incidence density for reinfection was 9.4 (95% confidence interval [CI] 3.9‐22.6) and for primary infection the density was 9.1 (95% CI 7.9–10.5) cases/100, 000 patient days. Two recipients had immunity evaluated in the weeks prior to reinfection, by measuring immunoglobulin‐G (IgG) antibody titer to the SARS‐CoV‐2 receptor binding domain and virus‐specific CD4+ and CD8+ T‐cell reactivity following stimulation with SARS‐CoV‐2 peptide pools. Both mounted virus specific CD4 T‐cell responses prior to reinfection (1.19% and 0.28% of total CD4 T cells) and both had reactive IgG testing (1.30 and 4.99 signal/cut off ratio). Conclusions: This suggests that SOT recipients infected with SARS‐CoV‐2 remain at high risk for reinfection even after generating cellular and humoral immune responses. Abstract : Among the cohort of patients who received a solid‐organ transplant (SOT) at our center, we studied the incidence density of SARS‐CoV‐2 reinfection among those with prior SARS‐CoV‐2 infection ( n  = 210). Patients were studied while on immunosuppression for an active graft. The study period included the first month after local detection of the Delta variant and prior to the emergence of the Omicron variant. Reinfection was defined according to CDC recommendations (> 90 days interval), although serial cycle threshold values were used in lieu of genomic sequencing, which was not available. In the upper right, incidence density is shown for three groups: 1.) the entire cohort (including those with initial infection prior to SOT) 2.) the subset with both infections after SOT and 3.) background rate of new primary infections among SOT during the study period. In parallel, a prospective immunity study had obtained serology and T‐cell immunity data in SOT recipients about 6 months after SARS‐CoV‐2 infection, and in two participants this was just prior to reinfection—data shown in lower right.